Motorcycle accident injuries are more severe than other land transportation injuries (Universa Medicina, 2018)
BackgroundInjuries due to traffic accidents are the leading cause of death and disability, especially in developing countries. The proportion of injuries in Indonesia tends to increase. The cause of the injury is dominated by motorcycle accidents (70-85%). The aim of this study was to compare the severity of motorcycle injuries with that of other land transportation injuries in Indonesia. MethodsA study of a cross-sectional design was performed involving 15,849 subjects from 33 provinces in Indonesia. The dependent variable was the severity of injury and the main independent variable was transportation mode (motorcycle and other vehicles). Other independent variables included were respondent characteristics (sex, age, education, occupation, economic status) and health status (stroke, hypertension, heart disease, impaired hearing and vision). Chi-square test and multiple logistic regression were used to analyze the data.ResultsThe contribution of motorcycle transportation mode to the severity of the injury was 85.5%. The proportion of severity of injury due to motorcycle transportation was higher (9.0%) than to other land transportation modes (7.5%). The severity of injuries related to motorcycle transportation was 1.1 times greater (AOR=1.1 95% CI 1.0-1.3) than that other related to vehicles. The determinants of severity of injury due to motorcycle transportation were age and sex.Conclusion Motorcyclists are at higher risk of having injuries than persons using other modes of transportation. Motorcyclists need to increase the safety of riding and to be more discriminating in the selection of the safest mode of transportation, by taking age and sex into consideration.